2019
DOI: 10.1007/s00011-019-01295-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-802 alleviates lipopolysaccharide-induced acute lung injury by targeting Peli2

Abstract: Introduction Acute respiratory distress syndrome (ARDS) is a life-threatening medical condition. It is characterized by serious lung inflammation or injury. Characterizing novel miRNAs implicated in ARDS pathogenesis may provide new therapeutic strategy for managing ARDS. Methods We employed LPS-induced lung injury model to profile miRNAs associated with ARDS. We isolated one miRNA candidate and characterized its role in lipopolysaccharide (LPS)-induced proinflammatory cytokine production in lung macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Previous studies have verified that PELI2 plays a role in lung injury caused by sepsis [ 44 ], which mechanism might be related to PELI2 activation. In our study, PELI2 was predicted to be a direct downstream target of Mir-128-3P, which is associated with apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have verified that PELI2 plays a role in lung injury caused by sepsis [ 44 ], which mechanism might be related to PELI2 activation. In our study, PELI2 was predicted to be a direct downstream target of Mir-128-3P, which is associated with apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…PELI2, a positive regulator in LPS/TLR4 pathway, has been suggested to play a role in IL-1/LPS-induced activation of ERK and JNK MAPK pathways and increased stabilization of mRNAs encoding pro-inflammatory proteins [ 29 , 30 ]. You et al found that PELI2 was upregulated in acute respiratory distress syndrome model, and miR-802 carried a protective role against LPS-induced ALI by downregulating PELI2 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-802 possesses multiple functions. It has been reported to regulate cancer development, alleviate lipopolysaccharide-induced acute lung injury, and modulate the expression of human angiotensin II type I receptor (27)(28)(29). In terms of metabolism, miR-802 impairs glucose metabolism and causes nephropathy in both mice and humans with obesity (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that miRNAs, as gene expression switches, have an important role in the progression of ALI (18,19). A recent study has indicated that miR-802 was expressed at a low level in LPS-induced ALI and alleviated LPS-induced ALI by targeting Peli2 (20). Another recent study has revealed that miR-539-5p was underexpressed in sepsis-induced ALI and could protect mice from ALI (21).…”
Section: Discussionmentioning
confidence: 99%